2022
DOI: 10.3389/fimmu.2022.984408
|View full text |Cite
|
Sign up to set email alerts
|

Solute carrier nutrient transporters in rheumatoid arthritis fibroblast-like synoviocytes

Abstract: Metabolomic studies show that rheumatoid arthritis (RA) is associated with metabolic disruption. Metabolic changes in fibroblast-like synoviocytes (FLS) likely contribute to FLS abnormal response and strongly contribute to joint destruction. These changes often involve increased expression of nutrient transporters to meet a high demand for energy or biomolecules. The solute carrier (SLC) transporter families are nutrient transporters and serve as ‘metabolic gates’ for cells by mediating the transport of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Meta-analysis and genome-wide association study by Ben Hamda C. et al 16 showed SLC7A5 as one of the top shared upregulated DEGs in the meta-analysis that is from the same solute carrier family as solute carrier family 4 member 1 (SLC4A1) and as our top DEG SLC44A5 downregulated and overlapping in SCD non-treated over HC and SCD treated over HC. The solute carrier transporter families are known as metabolic "gatekeepers" of the cells with an important role in adaptive and innate immunity 39 . SLC4A1 also encodes Band 3 an important mebrane transporter protein in red cells, highlighting its role in membrane stability and anione transport in erythropoietic cells 15 , Human SLC4A1/AE1 mutations are known to cause human spherocytosis and stomatocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis and genome-wide association study by Ben Hamda C. et al 16 showed SLC7A5 as one of the top shared upregulated DEGs in the meta-analysis that is from the same solute carrier family as solute carrier family 4 member 1 (SLC4A1) and as our top DEG SLC44A5 downregulated and overlapping in SCD non-treated over HC and SCD treated over HC. The solute carrier transporter families are known as metabolic "gatekeepers" of the cells with an important role in adaptive and innate immunity 39 . SLC4A1 also encodes Band 3 an important mebrane transporter protein in red cells, highlighting its role in membrane stability and anione transport in erythropoietic cells 15 , Human SLC4A1/AE1 mutations are known to cause human spherocytosis and stomatocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Energy metabolism plays a crucial role in the stress adaptation and tolerance response of organisms, as extra energy is required to recover from and maintain the internal balance [ 80 ]. As the transporter proteins, the SLC family plays a significant role in maintaining the cellular metabolism and energy supply [ 81 , 82 , 83 ]. The identified genes ( Slc16a2 , Slc16a9 , Slc16a12 , Slc16a14 ) in our research belong to the Slc16a family, which is a group of transmembrane transport proteins mainly involved in the transport of organic acids such as lactate and pyruvate [ 81 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…These activities promote the activation of FLS in multiple ways, whereas the use of related metabolic process inhibitors can reduce FLS migration, reducing bone erosion and joint edema. Moreover, they can be used as innovative targets for treating RA by targeting and regulating the activation of SLC family members during the development of new drugs ( 66 ).…”
Section: Altered Fls Metabolism and Intracellular Signaling Pathway T...mentioning
confidence: 99%